2005
DOI: 10.1073/pnas.0504617102
|View full text |Cite
|
Sign up to set email alerts
|

Shoot circumnutation and winding movements require gravisensing cells

Abstract: Circumnutation and winding in plants are universal growth movements that allow plants to survive despite their sessile nature. However, the detailed molecular mechanisms controlling these phenomena remain unclear. We previously found that a gravitropic mutant of Japanese morning glory (Pharbitis nil or Ipomoea nil), Shidare-asagao (weeping), is defective not only in circumnutation but also in the winding response. This phenotype is similar to that of the Arabidopsis SCARECROW (SCR) mutant. We therefore investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 35 publications
4
62
1
1
Order By: Relevance
“…Nevertheless, the spaceflight study seemed to be definitive COMMENTARY and provides strong evidence that periodic growth oscillations (i.e., circumnutations) persist in the absence of significant gravitational accelerations. Thus, these results are in conflict with the study reported by Kitazawa et al (6). How do we reconcile these two reports and two hypotheses about the relationship between gravitropism and circumnutation?…”
contrasting
confidence: 57%
“…Nevertheless, the spaceflight study seemed to be definitive COMMENTARY and provides strong evidence that periodic growth oscillations (i.e., circumnutations) persist in the absence of significant gravitational accelerations. Thus, these results are in conflict with the study reported by Kitazawa et al (6). How do we reconcile these two reports and two hypotheses about the relationship between gravitropism and circumnutation?…”
contrasting
confidence: 57%
“…Gravitropic mutants (pgm1, scr2-1) of Arabidopsis thaliana and Pharbitis nil were defective in circumnutations so there was a link between circumnutation and gravitropism. [38][39][40] Investigations of auxin-resistant axr2-1 mutant of Arabidopsis supported the notion that auxin participates in circumnutation. 39 In Oryza sativa coleoptiles, phy A mutants that cannot express phyA were investigated to clarify the involvement of phytochromes in red light induced circumnutation inhibition.…”
Section: Mutants In Research On the Circumnutation Mechanismmentioning
confidence: 72%
“…44 The endodermal cells (statocytes with amyloplasts functioning as statoliths) also play an important role in circumnutations, as revealed by scr mutants of Arabidopsis and Pharbitis nil. 38,39 Plasmodesmata, by which cells create a continuous system (symplast) facilitating intercellular communication, are equally important. Brown' circumnutation model 33 Circumnutation related to Ca 2+ -dependent protein kinases; it may also stimulate the activity of cytoskeleton elements.…”
Section: Cellular and Molecular Basis For Circumnutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus at least it seems reasonable to assume the existence of an internal oscillator mechanism that is affected by gravitational stimuli (Johnsson, 1997). Recently it has been reported that a gravitropic mutant of Japanese morning glory (Pharbitis nil or Ipomoea nil), Shidare-asagao (weeping), is also defective in circumnutation, and that both defect of circumnutation and abnormal gravitropism are attributable to a loss of PnSCR (SCARECROW) function, suggesting that shoot circumnutation requires gravisensing endodermal cells (Kitazawa et al, 2005).…”
Section: Graviresponse In Plants: Automorphosis Autotropism and Automentioning
confidence: 99%